Large‐acceptance diamond planar refractive lenses manufactured by laser cutting. (1st January 2015) - Polikarpov, Maxim; Snigireva, Irina; Morse, John; Yunkin, Vyacheslav; Kuznetsov, Sergey; Snigirev, Anatoly
<x xml:space="preserve">Abstract</x> For the first time, single‐crystal diamond planar refractive lenses have been fabricated by laser micromachining in 300 µm‐thick diamond plates which were grown by chemical vapour deposition. Linear lenses with apertures up to 1 mm and parabola apex radii up to 500 µm were manufactured and tested at the ESRF ID06 beamline. The large acceptance of these lenses allows them to be used as beam‐conditioning elements. Owing to the unsurpassed thermal properties of single‐crystal diamond, these lenses should be suitable to withstand the extreme flux densities expected at the planned fourth‐generation X‐ray sources.